Qanun Jinayat Aceh dalam Perspektif Hak Asasai Manusia: Studi Kasus Putusan Mahkamah Agung Nomor 60 P/HUM/2015 - Abdul Karnaen (Universitas Kuningan, 2025)
The Aceh Qanun is a regional legal instrument born from the uniqueness and privileges of Aceh within the framework of the Unitary State of the Republic of Indonesia. The position of the qanun as a special regional regulation has given rise to debate, particularly regarding its authority over the law and its material review mechanism. This study aims to analyze the legal arrangements of the authority of the Aceh Qanun within the national legal system and to examine the application of the Supreme Court decision in the case of the material review of the Aceh Qanun, particularly the Jinayat Qanun. The research method used is normative juridical with a statutory approach and a conceptual approach. The results of the study indicate that hierarchically the Aceh Qanun is placed on an equal footing with provincial regulations but has substantive specificity based on Law Number 11 of 2006 concerning the governance of Aceh. In addition, the Supreme Court has the authority to conduct a material review of the qanun if it is suspected of contradicting higher laws. Supreme Court Decision No. 60 P/HUM/2015 demonstrates that the Supreme Court considered the authority, hierarchy of norms, and Aceh's specific characteristics in assessing the applicability of the Aceh Qanun Jinayat. Therefore, the judicial review of the Aceh Qanun serves as a judicial oversight mechanism to maintain a balance between special autonomy and the supremacy of national law.